Desain Alat Pirolisis Reaktor Tunggal Untuk Daur Ulang Sampah Plastik - Pah, Jack C.A.; Adoe, Dominggus Godlief Heryson; Fahik, Emanuel Don (Universitas Nusa Cendana, 2023)
The purpose of this study was to determine the effect of media variations of 90% kusambi charcoal and 10% Plastic is a component that is difficult to separate from everyday human activities because of the various advantages it has. The more people consume, the more plastic waste they produce. To overcome this, of course, a way is needed to process the plastic waste into things that are more useful and also have benefits for nature, one way is by recycling the plastic waste into fuel, namely fuel in the form of oil. The benefit of this research is to produce fuel oil products from Polypropylene (PP) plastic waste as an alternative energy source by utilizing pyrolysis technology. Pyrolysis is a process for converting Polypropylene (PP) plastic waste into liquid fuel. The end result of this research is in the form of detailed images of the tool, the design of the tool, and the results of the testing process on the tool in the form of data on the quantity of oil in each test